Analisis Pelanggaran UNCLOS Terhadap Penangkapan Ikan Menggunakan Alat Tangkap Ilegal di Kepulauan Riau - Eka Yunita; Shila Wida Yuwansa; Sri Devi Kristin Sinaga (Public Knowledge, 2024)
This journal analyzes violations of the United Nations Convention on the Law of the Sea (UNCLOS) in the context of illegal fishing using unauthorized fishing gear in the Riau Islands, Indonesia. The research reveals serious impacts on the marine ecosystem and the sustainability of regional fishery resources. The UNCLOS legal analysis provides a foundation for evaluating these violations and their implications in international relations. These findings underscore the importance of international maritime law enforcement and inter-country cooperation in safeguarding the marine environment and maintaining fisheries sustainability in this region.